Efficacy of garlic extract and sodium hypochlorite on dental pulp dissolution: An in vitro study - S Anitha Rao; Lakkireddy Sunitha; B Nageshwar Rao; J Praveena Naik; V Chandra Shekar (Wolters Kluwer Medknow Publications, 2017)
Aim: The present study was aimed to assess and compare the human pulp dissolution capacity of sodium hypochlorite (NaOCl) (2.5%) and garlic extract. Materials and Methods: Several pulp tissues are obtained from both endodontically treated teeth and also by orthodontically extracted premolar teeth and were sectioned with a surgical blade into seventy-five pieces of same size and weight. Pulp tissues were then divided into Allium sativum extract (ASE) group, NaOCl group, and NaCl group and tissues were immersed in the test solutions for 30, 60, and 90 min, respectively. Further tissues were weighed using a precision balance at tested intervals, and the percentage weight loss was calculated and statistically analyzed. Results: In this study, pulp tissue treated with 2.5% NaOCl solution at all tested time intervals showed significant (P < 0.001) pulp tissue dissolution capacity and a maximum of dissolution was observed at 90 min. Pulp tissue treated with ASE showed little dissolution ability at all tested time periods. Whereas, 0.9% NaCl showed no ability to dissolve human pulp tissue. Conclusion: It can be concluded that 2.5% NaOCl had the maximum tissue dissolving capacity when compared to different concentrations of ASE. Saline had no effect on the human pulp dissolution.